Ключевые идеи русской языковой картины мира и межкультурная коммуникация - Шмелев, А.Д. (Культура народов Причерноморья, 2003)
В статье рассматриваются основные идеи русской языковой картины мира. У статті розглянуто основні ідеї російської мовної картини світу. The paper deals with key ideas of Russian linguistic model of the world. An attempt is made to reveal a network of language-specific values and attitudes, embodied in words, derivational patterns, grammatical constructions, common conversational routines.